O Conselho de Classe: a participação da comunidade escolar - Vargas, Maria Angela Serafini (2008)
The research The Council of Class: the participation of the school community, suggests the question: it is possible to develop a participatory democratic management in the public school of Basic Education? For understanding, the relevance of the question, the work had as objective to demonstrate, that a public school of Basic Education of the periphery of Maringá, although the challenges faced for the managing team, obtained the participation of all involved team in the Council of Class: managers, professors, employees, pupils, parents and representatives of the community. Proposals had been elaborated that made possible the accomplishment of in pedagogical work as the necessities of the process education learning, aiming at a more efficient education in classroom. The work, for its nature, involving a public school of the Paraná, had as it has supported the qualitative research, through the Study of Case, focusing the phenomena happened in the day the day for the managing team, considering excellent for the meetings of the Council of Class. The used instruments of the research, beyond a bibliography that based the theoretical part of the subject, had served as study objects the acts of the meetings of the Council of Class, the regiment, the project pedagogical politician, the reports of the series of the involved pupils. Of ownership of these elements and the gotten data of the documentary analysis, relation was evidenced mainly that, if it will not have a full democratic management, it had significant advances in the integration school community through the participation of the team of the school and the representatives of the community, special way of the parents in the guiding of solutions as indiscipline, works of the pupils, insufficient income, progress in the learning and, school and family, the main involved institutions in the education. It was arrived the conclusion that, gradual, has possibility of if constructing a more democratic school, with the persistence of all its team and of the community, in the quarrel and solutions of the problems, aiming at always the taking of decisions and the transformations of the pedagogical actions.